2017
DOI: 10.1002/pon.4567
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control, optimism, and recollections of depression and self‐reported cognitive functioning following treatment for colorectal cancer

Abstract: Neither internal locus of control nor optimism in colorectal cancer survivors influences correlation between cognition and depression. Health care providers should note individual differences in responses to treatment and be alert to the impact of depression on perceived everyday functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
4
2
Order By: Relevance
“…The findings of this systematic review have provided evidence for factors affecting psychosocial adjustment to colorectal cancer. Previous research has highlighted that those participants with an internal locus of control can adjust better to living with colorectal cancer as a chronic illness (Mititelu, 2016;Wilson, 2017). However, our results indicate that both internal locus of control and external locus of control can help with adjustment.…”
Section: Discussioncontrasting
confidence: 73%
“…The findings of this systematic review have provided evidence for factors affecting psychosocial adjustment to colorectal cancer. Previous research has highlighted that those participants with an internal locus of control can adjust better to living with colorectal cancer as a chronic illness (Mititelu, 2016;Wilson, 2017). However, our results indicate that both internal locus of control and external locus of control can help with adjustment.…”
Section: Discussioncontrasting
confidence: 73%
“…Both were found to have a major effect on the outcomes of coping with adversity . Some previous studies reported associations between subjective stress or optimism and emotional distress, fatigue, and cognitive difficulties; other studies reported that optimism predicted the course of symptoms over time . However, the present study is unique in its assessment of the extent to which change in psycho‐social parameters affects postchemotherapy symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies found an association between a high level of optimism and reduced levels of fatigue, while in another study with various types cancer patients undergoing chemotherapy, no such association was reported. Several studies found either an association between optimism and cognitive difficulties in individuals with various types of cancer or no association . While most studies refer to optimism as a dispositional and relatively stable trait, it has also been shown that levels of optimism may change over time in response to life events, such as cancer …”
Section: Introductionmentioning
confidence: 99%
“…Oncological patients who consider that they have little control over their disease can feel more comfortable and safe delegating control to their oncologist (Helmes et al, 2002). Current studies found that the external LOC seemed to be associated with a lower prevalence of depression in cancer patients (Aarts et al, 2015; Wilson et al, 2018).…”
Section: Discussionmentioning
confidence: 98%